Design, synthesis, and antifungal activity of novel dithiin tetracarboximide derivatives as potential succinate dehydrogenase inhibitors. Issue 5 (1st February 2023) - Ma, Zhi; Qiu, Shuo; Zhang, Dong; Guo, Xinying; Lu, Yuele; Fan, Yongxian; Chen, Xiaolong
Abstract: BACKGROUND: Succinate dehydrogenase inhibitor (SDHI) fungicides are an important class of agricultural fungicides with the advantages of high efficiency and a broad bactericidal spectrum. To pursue novel SDHIs, a series of N ‐substituted dithiin tetracarboximide derivatives were designed, synthesized, and characterized by 1 H NMR, 13 C NMR, and high resolution mass spectrum (HRMS). RESULTS: These engineered compounds displayed potent fungicidal activity against phytopathogens, including Sclerotinia sclerotiorum, Botrytis cinerea, and Rhizoctonia solani, comparable with that of the commercial SDHI fungicide boscalid . In particular, compound 18 stood out with prominent activity against S. sclerotiorum with a half‐maximal effective concentration (EC50 ) value of 1.37 μg ml −1 . Compound 1 exhibited the most potent antifungal activity against B. cinerea with EC50 values of 5.02 μg ml −1 . As for R. solani, 12 and 13 exhibited remarkably inhibitory activity with EC50 values of 4.26 and 5.76 μg ml −1, respectively. In the succinate dehydrogenase (SDH) inhibition assay, 13 presented significant inhibitory activity with a half‐maximal inhibitory concentration (IC50 ) value of 15.3 μm, which was approximately equivalent to that of boscalid (14.2 μm ). Furthermore, molecular docking studies revealed that 13 could anchor in the binding site of SDH. CONCLUSION: Taken together, results suggested that the dithiin tetracarboximide scaffold possessed a huge potential to be developed as novel fungicides and SDHIs. © 2023 Society of Chemical Industry. Abstract : Compounds 13 displayed potent fungicidal activities against Sclerotinia sclerotiorum, Botrytis cinerea, and Rhizoctonia solani, comparable with that of the commercial succinate dehydrogenase inhibitor fungicide boscalid . Furthermore, 13 presented significant succinate dehydrogenase's (SDH) inhibitory activity with a half‐maximal inhibitory concentration of 15.3 μm . Molecular docking analysis revealed that 13 could anchor in the binding site of SDH.